Chinese Herbal Medicines as an Adjunctive Therapy for Unresectable Pancreatic Cancer: A Systematic Review and Meta-Analysis. (23rd November 2015) - Li, Bin; Gan, Run; Yang, Quanjun; Huang, Jinlu; Chen, Pengguo; Wan, Lili; Guo, Cheng
Abstract : Pancreatic cancer is a common malignancy with a high mortality. Most patients present clinically with advanced pancreatic cancer. Moreover, the effect of radiotherapy or chemotherapy is limited. Complementary and alternative medicines represent exciting adjunctive therapies. In this study, we ascertained the beneficial and adverse effects of Chinese herbal medicine (CHM) in combination with conventional therapy for inoperable pancreatic cancer by using meta-analysis methods for controlled clinical trials. We extracted data for studies searched from six electronic databases that were searched and also assessed the methodological quality of the included studies. We evaluated the following outcome measures: 6-month and 1-year survival rate, objective response rate, disease control rate, quality of life, and adverse effects. The final analysis showed CHM is a promising strategy as an adjunctive therapy to treat advanced or inoperable pancreatic cancer and that CHM in combination with conventional therapy is a promising strategy for resistant disease. However, convincing evidence must be obtained and confirmed by high-quality trials in future studies.